TuMV infection alters the regulation of miR168/AGO1 and miR403/AGO2 systems in Arabidopsis - Manacorda, Carlos Augusto; Tasselli, Sabrina; Marano, María Rosa; Asurmendi, Sebastian (Springer, 2024)
Plant argonaute (AGO) proteins—chiefly AGO1 and 2—restrict viral infections. AGO1/2 also participate in developmental processes and are tightly regulated by microRNAs. Researchers have conducted extensive studies on the regulatory loop involving miR168/AGO1 in viral infections, though comparatively less attention has been given to the miR403/AGO2 system. Here, we simultaneously studied both regulatory systems in Arabidopsis plants infected with turnip mosaic virus (TuMV). TuMV simultaneously altered both miR168 and miR403 precursors as well as their mature forms at medium to late stages of infection. While TuMV decreased miRNA precursor molecules, it induced the overaccumulation of mature miRNA forms, without evidence of concomitant transcriptional alteration. The AGO1 protein remained at basal levels, whereas the AGO2 protein overaccumulated. The application of exogenous salicylic acid (SA) in healthy plants resulted in elevated AGO2 mRNA levels. Conversely, this hormone did not induce any significant changes in either AGO1 mRNA levels or those of miRs 168 and 403. This response is coherent with previous results, which showed enhanced levels of SA under TuMV infection and the partially differential sensitivity that AGO proteins have against this defense hormone. Our results also highlight the key role of AGO2 in leaves as an antiviral molecule and demonstrate the different responsiveness of the AGO1/miR168 and AGO2/miR403 systems regarding TuMV infection and SA response. Taken together, the results presented here are in line with previous reports studying abiotic and biotic impacts on microRNA biogenesis and AGO-dependent antiviral defense and further expand the knowledge of the miR403/AGO2 regulatory system.